The Emerald handbook of blockchain for business - Baker, H. Kent 1944-; Nikbakht, Ehsan; Stein Smith, Sean (Emerald handbooks, 2021)
Although an emerging technology, blockchain is here to stay. Since its inception, imaginative thinkers have identified new ways for this powerful technology to bring innovative solutions to problems in the business world. Considered by many as an extreme and disruptive change, how can business leaders overcome resistance to the implementation of blockchain solutions and maximize its potential? 'The Emerald Handbook of Blockchain for Business' equips academics, practitioners, and students with a broad understanding of the cutting-edge developments and applications of emerging blockchain technology. Covering the basic concepts while also showcasing practical applications in intricate real-world situations, this handbook bridges the gap between theory and practice, providing a useful balance of detailed and user-friendly coverage. Facilitating readers with a working knowledge of how blockchain functions and integrates within the business world, this handbook is essential reading for academics looking for a springboard for further research and practitioners needing a go-to resource for navigating the implementation of this fast-moving new technology.